BEAM Lesson Plan - (:unkn) unknown (My University, 2013)
This creative commons publication provides a lesson plan on writing with sources in an academic context. The plan is designed for use in a higher education setting and is aligned with AAC&U LEAP Value Rubric for Information Literacy and the Framework for Information Literacy in Higher Education.
Keywords: BEAM; ACRL Information Literacy Framework for Higher Education; Pedagogy; Critical Thinking; OER